Removal of Hydrolyzed Reactive Dyes from Cotton Fabric Using Spent H2O2: A Green Approach - Ahmed Shaikh, Irfan; Munir, Suhaira; Suhail, Erham; Jamil, Nadia; Qadir, Abdul (Asian Journal of Chemistry, 2015)
In this paper, the effectiveness of spent H2O2 bleach liquor was evaluated for the removal of hydrolyzed reactive dyes from cotton fabrics. This study was conducted with an aim to develop a new textile dyeing method with lesser amount of water and chemicals, without compromising quality of dyeing. In this context, spent bleach water from a textile factory was collected and used in wash-off step of reactive dyeing to ascertain colour fastness properties of selected reactive dyes. Four dyeings, using C.I. Reactive Yellow 145, C.I. Reactive Red 194, C.I. Reactive Blue 19 and C.I. Reactive Black 5,were carried out and dyed fabric samples were subjected to both conventional washing and new washing method containing spent H2O2 bleach liquor. Fabrics washed-off with both methods were compared in terms of washing fastness, rubbing fastness, change of colour and magnitude of total colour difference (DE*). The colour fastnesses properties and final shade of fabrics washed-off with spent bleach were found to be comparable to those washed-off conventionally. This study concludes that spent of H2O2 bleach is a potential candidate for removing the unfixed reactive dyes from cotton fabrics.